Prevention of Child Marriage to Create a Family Problem Badriyah Fayumi's Perspective - Hikmiyah, Hawa' Hidayatul (Minhaj: Jurnal Ilmu Syariah, 2024)
Early childhood marriage has many negative impacts, especially for girls. For girls aged 10 to 14 years. With the high school dropout rate, there are fewer job opportunities for women. Apart from being a wife, sexual partner or taking care of children, quite a few women still want to have a career at work. Psychological and mental problems also cannot be underestimated. At an immature age, quarrels will often occur and often lead to violence, both physical and verbal. This researcher uses a juridical analysis approach because the study or research context uses cases in the field and is analyzed using legislation. If you look at this research based on its type, this research uses a type of library research. The data used are books about child marriage and the mashlahah family. Men and women must be able to work together and live in harmony. One form of cooperation and the embodiment of harmonious living is marriage. Humans marry and build households. In fact, it's not just humans who marry or pair up, all creatures have partners. As stated in QS.Adz-Dzariyat 51: 49 which means "we have created everything in pairs so that you remember" and also in QS.Yasin 36:36 which says truly! "Glorified is He who created all pairs, both from what the earth grows and from themselves (humans) and from (creatures) that they do not know." A marriage must form family functions.